1970
DOI: 10.3329/bjo.v14i2.3279
|View full text |Cite
|
Sign up to set email alerts
|

Noise induced hearing loss among the textile industry workers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Most workers had less than 10 years of service duration in the jute mills. This finding was also consistent with similar studies conducted in Turkey and Bangladesh 16,19 . However, the other studies stated that more than 10 years of service duration occurred in a large proportion of workers 14,17 .…”
Section: Resultssupporting
confidence: 93%
“…Most workers had less than 10 years of service duration in the jute mills. This finding was also consistent with similar studies conducted in Turkey and Bangladesh 16,19 . However, the other studies stated that more than 10 years of service duration occurred in a large proportion of workers 14,17 .…”
Section: Resultssupporting
confidence: 93%
“…These findings are on the same line with Haider et al (2008) who carried out a study about noise induced hearing loss among The Textile Industry Workers and revealed that noise was one of the common physical and environmental risks in the workplace Moreover, Sheha (2009) who conducted a study about Occupational Hazards among Workers in Glass Manufactures Industries, reported that noise hazard had the highest share of physical hazard exposure, followed by extreme temperature exposure.…”
Section: Discussionsupporting
confidence: 52%
“…This was consistent with other findings looking at NIHL among workers exposed to similar level of noise at the workplace. [24][25][26] Teixera et al, 17 who studied hearing loss among vector control workers in Brazil, have obtained a higher prevalence of 66.7% among those who were exposed to noise at work or leisure. The prevalence obtained by Teixera et al was much higher compared with this study as the operational definition adopted by Teixera et al was different.…”
Section: Discussionmentioning
confidence: 99%